The Effectiveness of Inheritance Dispute Resolution Seen from Medan District Court Decision Number 43/pdt. G/2020/PN Mdn - Louis Sebastian Anot Putra; Mia Hadiati; Grace Avianti; Maria Franciska Limanto; Kent Edward Liem (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This journal contains the effectiveness of inheritance dispute resolution based on the view of civil law, if talking about inheritance law, there will be 3 types of inheritance law that are often used in Indonesia, but in this journal the discussion will focus on dispute resolution through civil court. This journal takes Medan District Court Decision Number 43/pdt. G/2020/PN Mdn about a mother who sued her child for improper distribution of inheritance, in this journal also discussed the specific effectiveness of the settlement and the rights of adopted children in cases of inheritance disputes, in this journal also contains laws and articles in the Civil Code that can help readers understand the regulations regarding civil inheritance law.